2012
DOI: 10.1128/aac.06305-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparative In Vitro Activities of LFF571 against Clostridium difficile and 630 Other Intestinal Strains of Aerobic and Anaerobic Bacteria

Abstract: ABSTRACTThein vitroactivities of LFF571, a novel analog of GE2270A that inhibits bacterial growth by binding with high affinity for protein synthesis elongation factor Tu, fidaxomicin, and 10 other antimicrobial agents were determined against 50 strains ofClostridium difficileand 630 other anaerobic and aerobic organisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 21 publications
2
40
0
Order By: Relevance
“…8, compound 3), a semisynthetic thiopeptide that is an inhibitor of bacterial translation acting via inhibition of elongation factor Tu (250). This compound possesses potent activity against C. difficile and most other Gram-positive anaerobes, displaying MIC 90 values of Յ0.25 g/ml, with the exception of bifidobacteria and lactobacilli (251). Recently a phase 1 first-in-human clinical trial investigated the safety and pharmacokinetics of single and multiple ascending oral doses of LFF571 in healthy subjects in a randomized, double-blind, placebo-controlled study (252).…”
Section: Lff571mentioning
confidence: 99%
“…8, compound 3), a semisynthetic thiopeptide that is an inhibitor of bacterial translation acting via inhibition of elongation factor Tu (250). This compound possesses potent activity against C. difficile and most other Gram-positive anaerobes, displaying MIC 90 values of Յ0.25 g/ml, with the exception of bifidobacteria and lactobacilli (251). Recently a phase 1 first-in-human clinical trial investigated the safety and pharmacokinetics of single and multiple ascending oral doses of LFF571 in healthy subjects in a randomized, double-blind, placebo-controlled study (252).…”
Section: Lff571mentioning
confidence: 99%
“…Recently, two large doubleblind phase III trials showed that the antibiotic fidaxomicin was noninferior to vancomycin treatment regarding clinical cure rates and was associated with substantially lower rates of recurrent CDI (5)(6)(7). Several mechanisms may mediate the beneficial effects of fidaxomicin in CDI, including antimicrobial activity against C. difficile strains (8)(9)(10), which is due to inhibition of the transcription of bacterial RNA by RNA polymerases (11), and reduction of toxin A and B production by C. difficile (12).…”
mentioning
confidence: 99%
“…Favorably, 5FDQD is less active than fidaxomicin against the Bifidobacterium, Lactobacillus, and Actinomyces strains tested herein. Likewise, the MICs of 5FDQD against representatives of these genera are higher than the published MICs of fidaxomicin, vancomycin, metronidazole, and two clinical development candidates for CDI treatment-LFF-571 and surotomycin (39,41,58,81). Thus, the spectrum of 5FDQD appears to be narrower than those of established and developmental CDI therapeutics and should theoretically permit the regrowth of intestinal flora that protect against recurrence.…”
Section: Resultsmentioning
confidence: 84%